Pulling the Brakes on Political Violence: How Internal Brakes Limited Violent Escalation from the Provisional IRA in Pre- and Post-Good Friday Northern Ireland - Dowling, Jennifer (Terrorism and political violence, 2024)
Under what circumstances do paramilitary groups place limits on their use of political violence? This article considers why one of the most prominent paramilitary groups active during the “Troubles” in Northern Ireland, the Provisional IRA (PIRA), exercised restraint and limited their use of political violence, both in the lead up to, and in the wake of the Good Friday Agreement. It applies Busher, Holbrook, and Macklin’s “internal brakes” typology to understand why despite the PIRA’s proven capacity to sustain a campaign of armed violence for more than thirty years, they reined in on paramilitarism during the 1990s peace process. Through the lens of various brakes, the analysis identifies seven developments that were particularly salient in limiting the PIRA’s use of armed violence. These developments included: a weakened capacity to continue their armed campaign, waning popular support, an opening of political opportunities, the need to maintain ties with strategically important non-violent allies, the gradual softening of out-group boundaries, the decommissioning process, as well as the creation of spaces for non-violent activism within the wider movement. This study’s findings contribute to the scholarly debate on understanding how militant groups manage the parameters of their violence, highlighting several factors that may mitigate the risk of extremist views escalating to political violence.